Study of Bacterial Contamination in Katingan River in Katingan Hilir Subdistric - Rahman, Luthfi Aulia; Ayatusa'adah, Ayatusa'adah; Swestyani, Sondra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
River water pollution is caused by waste, particularly bacterial contamination resulting from a variety of waste types generated by community activities on the river coast. Stream water that is sullied with microbes, whenever utilized reasonably, will be exceptionally risky for the strength of stream seaside networks. The most elevated instances of looseness of the bowels were in Katingan Rule at 4,920 individuals/year. This research aims to determine the type and value of coliform bacterial contamination in the waters of the Katingan River, Kasongan Lama Village, Katingan Hilir District. This research uses quantitative methods. The Katingan river water is cloudy brown, has no aroma, has a turbidity value of 50, which is strongly suspected to be high turbidity, and has a water pH of 3.3, which is strongly suspected to be acidic. All examples from the examination results were positive with a typical MPN worth of >1100 MPN/g and had a place with bar molded gram-negative microbes (bacilli) and were thought to be explicitly Escherichia Coli. The experimental outcomes show that the waters of the Katingan Stream, Kasongan Lama Town, Katingan Hilir Region, are decidedly defiled with coliform microscopic organisms and have passed the edge for class 1 waterway prerequisites (1000 MPN/g).